Identification of Quantitative Trait Loci Associated With Iron Deficiency Tolerance in Maize - Xu, Jianqin; Zhu, Xiaoyang; Yan, Fang; Zhu, Huaqing; Zhou, Xiuyu; Yu, Futong (Frontiers in Plant Science, 2022)
Iron (Fe) is a limiting factor for crop growth and nutritional quality because of its low solubility. However, the current understanding of how major crops respond to Fe deficiency and the genetic basis still remains limited. In the present study, Fe-efficient inbred line Ye478 and Fe-inefficient inbred line Wu312, and their recombinant inbred line (RIL) population were utilized to reveal the physiological and genetic responses of maize to low Fe stress. Compared with the Fe-sufficient conditions (+Fe: 200 μmol L-1), Fe-deficient supply (-Fe: 30 μmol L-1) significantly reduced shoot and root dry weights, leaf SPAD of Fe-efficient inbred line Ye478 by 31.4%, 31.8% and 45.4%, respectively; decreased Fe-inefficient inbred line Wu312 by 72.0%, 45.1% and 82.6%, respectively. Under Fe deficiency, compared with the supply of calcium nitrate (N1), equally supplying ammonium nitrate (N2) significantly increased the shoot and root dry weights of Wu312 by 37.5% and 51.6%, respectively; and enhanced Ye478 by 23.9% and 45.1%, respectively. Compared with N1, N2 resulted in 70.0% decrease of the root Fe concentration for Wu312 in the -Fe treatment, N2 treatment reduced the root Fe concentration of Ye478 by 59.5% in the -Fe treatment. These findings indicated that compared with only supplying nitrate nitrogen, combined supply of ammonium nitrogen and nitrate nitrogen not only contributed to better growth in maize, but also significantly reduced Fe concentration in roots. In linkage analysis, ten quantitative trait loci (QTLs) associated with Fe deficiency tolerance were detected, explaining 6.2 - 12.0% of phenotypic variation. Candidate genes considered to be associated with the mechanisms underlying Fe deficiency tolerance were identified within single locus or QTL co-localizations, including ZmYS3, ZmPYE, ZmEIL3, ZmMYB153, ZmILR3, ZmNAS4, which may form a sophisticated network to regulate the uptake, transport and redistribution of Fe. Furthermore, ZmYS3 was highly induced by Fe deficiency in the roots, ZmPYE and ZmEIL3 which may be involved in strategy I Fe acquisition were significantly upregulated in the shoots and roots under low Fe stress, ZmMYB153 was Fe-deficiency inducible in the shoots. Our findings will provide a comprehensive insight into the physiological and genetic basis of Fe deficiency tolerance.